PENGARUH LOVE OF MONEY DAN KEADILAN PAJAK TERHADAP TAX EVASION DENGAN BUDAYA SIRI’ NA PACCE SEBAGAI PEMODERASI - Jumiati Haerudin; Lince Bulutoding; Raodahtul Jannah (ISAFIR: Islamic Accounting and Finance Review, 2022)
This study aims to examine the effect of love of money and tax justice on tax evasion with the siri' na pacce culture as moderating (a case study of individual taxpayers registered at KPP Pratama South Makassar). This type of research is quantitative primary data with a causal associative approach. The population in this study are taxpayers registered at the South Makassar KPP Pratama. With a non-probability purposive sampling technique, the sample was collected by distributing questionnaires to respondents who happened to be met at the time this research was conducted. Research respondents determined by the Slovin formula amounted to 100 people. This study uses multiple linear regression analysis. The research results show that the love of money variable has a significant positive effect on tax evasion, while the tax equity variable has a negative effect on tax evasion. In addition, the siri'na pacce cultural variable can only moderate the influence of the love of money variable on tax evasion, while the effect of the tax justice variable on tax evasion cannot be moderated by the siri' na pacce culture.